Self-esteem, Body Image, and Dating Violence in Colombian Adolescents and Young Adults - Bolívar-Suárez, Yolima (Journal of interpersonal violence, 2022)
Two objectives were formulated. The first was to establish whether characteristics such as self-esteem, perception of body image, and dating perpetration explain dating victimization. The second was to check if sex moderates the relationship between low self-esteem and dissatisfaction and if body dissatisfaction mediates the effect of low self-esteem on being a victim of dating violence (DV). A total of 1,409 Colombian adolescents and young adults, secondary and university students (42.5% men and 57.5% women), aged between 14 and 25 years (M = 18.6 years; SD = 2.8 years) participated. An explanatory correlational design was used, in which the Rosenberg Self-Esteem Scale, the Body Shape Questionnaire, and the Revised Dating Violence Questionnaire were applied. Six regression models were proposed for both men and women, where it was found that low self-esteem, body dissatisfaction, and violence exerted in the courtship explain the violence received. Also, through the moderated mediation analysis, a moderate conditional indirect effect was verified of low self-esteem in DV victimization (R2 = 0.052***) through body dissatisfaction, being higher in women than in men. The preceding points to the convenience of intervening on self-esteem and body image in adolescents and young victims of this type of violence and considering these aspects in prevention campaigns.